Improving menstrual equity in the USA: perspectives from trans and non-binary people assigned female at birth and health care providers. Issue 10 (2nd August 2022) - Lane, Benjamin; Perez-Brumer, Amaya; Parker, Richard; Sprong, Amelia; Sommer, Marni
Abstract: Menstruation research has largely focused on addressing menstrual management barriers facing cisgender women and girls in low and middle-income countries. Scant literature has assessed the menstrual management needs of trans and non-binary people assigned female at birth. To better understand these frequently invisibilised menstruation-related needs, we conducted a multi-method qualitative study in New York City which included: 17 in-depth interviews across trans and non-binary people ( n = 10) and health care providers who serve them ( n = 7); and seven anonymous post-interview participatory writing responses with trans and non-binary participants to further elucidate their lived experiences with menstrual management. Lack of health care provider transgender competency, public toilet design (i.e. gaps in cubicle doors and lack of in-cubicle menstrual product disposal bins), and the social dynamics of public toilets (i.e. work and school) were identified as significant barriers to managing menstruation safely and accessibly for trans and non-binary people. These findings have important implications for healthcare policy, public toilet legislation and advancing menstrual equity in the USA.